2001
DOI: 10.1111/1468-0335.00230
|View full text |Cite
|
Sign up to set email alerts
|

Industrial Concentration and Market Integration in the European Union

Abstract: Unlike previous cross-section studies which test predictions from the theory of industrial structure, we do not make an ex ante assumption about the geographical market at which competition takes place. We develop an econometric technique that endogenously determines whether the EU or member state is the appropriate market level for each industry, while also estimating a structural model of concentration and market size. Another novelty is that we use European national as well as aggregate EU data. Strong supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
27
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 15 publications
(14 reference statements)
4
27
0
Order By: Relevance
“…This paper has two main objectives. First, this industry study complements and reinforces earlier cross-section econometric work (Sutton, 1991;Lyons and Matraves, 1996;Robinson and Chiang, 1996;Lyons, Matraves and Moffatt, 1998). Specifically, by concentrating on the experience of an individual industry, we add to the case evidence accumulated for major national markets in the food and drink industry as detailed in Sutton (1991).…”
Section: Introductionmentioning
confidence: 53%
See 1 more Smart Citation
“…This paper has two main objectives. First, this industry study complements and reinforces earlier cross-section econometric work (Sutton, 1991;Lyons and Matraves, 1996;Robinson and Chiang, 1996;Lyons, Matraves and Moffatt, 1998). Specifically, by concentrating on the experience of an individual industry, we add to the case evidence accumulated for major national markets in the food and drink industry as detailed in Sutton (1991).…”
Section: Introductionmentioning
confidence: 53%
“…Mean concentration for industries characterised by both intensive advertising and R&D expenditure was 44% in the US and 40% in the EU market in 1987 (Lyons, Matraves and Moffatt, 1998). Table 6 shows that concentration is much lower in the pharmaceutical industry: 26% for the US, 19% for the EU.…”
mentioning
confidence: 99%
“…The empirical work in Sutton (1991) considered only advertising, but the approach has been applied by subsequent writers to both advertising and R&D (Robinson and Chiang, 1996, Lyons and Matraves, 1996, Symeonidis, 2000, Lyons, Matraves, and Moffatt, 2001, Giorgetti, 2003 Robinson and Chiang (1996) use separate estimations for industries with different types of competition. Sometimes also the slope coefficients are allowed to vary by industry type to test the second prediction.…”
Section: /Ln(s/σ)mentioning
confidence: 99%
“…average frontier (i.e., OLS estimation) has been used by Symeonides (2000), who found that the errors had a wrong skew to be based on a stochastic frontier, and by Lyons, Matraves, and Moffatt (2001), among others.…”
mentioning
confidence: 99%
“…If products are homogenous (in the Sutton terminology a high -industry), an entrant o ering a product with a higher quality, captures a relatively large market share as many consumers are interested in a superior product. In contrast, if products are distant substitutes (low -industry) a rm investing in improved 9 Lyons et al (2001) use engineering estimates based on the rms' technologies employed in the production process.…”
mentioning
confidence: 99%